Pristine GaFeO3 Photoanodes with Surface Charge Transfer Efficiency of Almost Unity at 1.23 V for Photoelectrochemical Water Splitting. Issue 8 (19th January 2023) - Sun, Xin; Wang, Min; Li, Hai‐Fang; Meng, Linxing; Lv, Xiao‐Jun; Li, Liang; Li, Meicheng
Abstract: Oxide‐based photoelectrodes commonly generate deep trap states associated with various intrinsic defects such as vacancies, antisites, and dislocations, limiting their photoelectrochemical properties. Herein, it is reported that rhombohedral GaFeO3 (GFO) thin‐film photoanodes exhibit defect‐inactive features, which manifest themselves by negligible trap‐states‐associated charge recombination losses during photoelectrochemical water splitting. Unlike conventional defect‐tolerant semiconductors, the origin of the defect‐inactivity in GFO is the strongly preferred antisite formation, suppressing the generation of other defects that act as deep traps. In addition, defect‐inactive GFO films possess really appropriate oxygen vacancy concentration for the oxygen evolution reaction (OER). As a result, the as‐prepared GFO films achieve the surface charge transfer efficiency ( η surface ) of 95.1% for photoelectrochemical water splitting at 1.23 V versus RHE without any further modification, which is the highest η surface reported of any pristine inorganic photoanodes. The onset potential toward the OER remarkably coincides with the flat band potential of 0.43 V versus RHE. This work not only demonstrates a new benchmark for the surface charge transfer yields of pristine metal oxides for solar water splitting but also enriches the arguments for defect tolerance and highlights the importance of rational tuning of oxygen vacancies. Abstract : Semiconductor surface commonly exhibits poor charge transfer for solar water splitting, which requires surface modification such as catalysis loading to enhance water redox kinetics. This article demonstrates that pristine rhombohedral GaFeO3 photoanodes without any further modification exhibit a record hole‐transfer efficiency for the oxygen evolution reaction at 1.23 V versus RHE.